The management of patients with autism in pediatric dental clinics: A review of the literature - Uchôa, Sue Ann Castro Lavareda; Corrêa, Suelen Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vânia Castro (Seven Editora, 2024)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition associated with significant behavioral changes. This condition, characterized by a heterogeneous range of symptoms, presents challenges in the context of pediatric dental care. The urgent need for a specialized approach in this scenario demands the presence of trained and specialized oral health professionals, able to employ effective methods to provide appropriate treatments to individuals with ASD. In view of these considerations, the objective of this study is to address the treatment of autistic patients in pediatric dental clinics. Given the nature of the disorder, which can compromise social interaction and, consequently, adversely influence the dental care process, the implementation of these techniques is crucial for the efficacy and efficiency of treatment. The substantial impact of the behavioral disorders inherent to ASD on the patient's social dynamics makes it imperative to adopt approaches that minimize anxiety and promote an environment conducive to collaboration between the professional and the child patient. Thus, it is intended not only to contribute to the specialized literature on the subject, but also to provide practical subsidies that allow a tangible improvement in the quality of care provided to this specific portion of the pediatric population. DOI: https://doi.org/10.56238/sevened2023.007-040